Penanganan Carpal Tunnel Syndrome Menggunakan Teknik Open Insicion - Filep Marfil Tarangi; Samuel Maruanaya (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Carpal tunnel syndrome (CTS) is a compression neuropathy condition that occurs due to compression of the median nerve at the wrist, often caused by repetitive motion or excessive pressure. CTS can cause symptoms such as pain, tingling, numbness and weakness in the hand, which can interfere with the quality of life. Conservative treatments, such as the use of splints and the administration of corticosteroids, are often effective in mild to moderate cases. However, in more severe cases of CTS that do not respond to conservative therapy, surgery becomes the main option. One of the commonly used surgical methods is the open incision technique, which aims to release compression on the median nerve by incising the carpal ligament. This case report discusses our experience in treating CTS with the open incision technique. Although this technique is more invasive, the long-term results are often satisfactory, with many patients experiencing good recovery. Open incision surgery remains an effective option for CTS patients who do not respond to conservative treatment